2020
DOI: 10.1016/j.adro.2020.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Single-Fraction Stereotactic Body Radiation Therapy: A Paradigm During the Coronavirus Disease 2019 (COVID-19) Pandemic and Beyond?

Abstract: Purpose Owing to the coronavirus disease 2019 (COVID-19) pandemic, radiation oncology departments have adopted various strategies to deliver radiation therapy safely and efficiently while minimizing the risk of severe acute respiratory syndrome coronavirus–2 transmission among patients and health care providers. One practical strategy is to deliver stereotactic body radiation therapy (SBRT) in a single fraction, which has been well established for treating bone metastases, although it has been inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 127 publications
1
35
0
Order By: Relevance
“…16 This may be related to a perceived increased risk of a geographic miss as well as increased toxicity when treating in a large single fraction, however these concerns have not been substantiated in published clinical outcomes. 5 In fact, several randomized single-vs multifraction trials for peripheral early stage NSCLC reported no significant difference in outcomes with long-term follow-up. 6 , 7 MR-guided SABR could facilitate broader use of single-fraction treatment by providing increased operator confidence in the accuracy of beam delivery to the target lesion throughout treatment by means of continuous intrafraction visualization with cine-MR. 13 Moreover, the streamlined workflow for treating in BH, or gated free breathing, without fiducial markers can substantially reduce the volume of normal tissue unnecessarily irradiated, and thus decrease the potential risk for serious toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 This may be related to a perceived increased risk of a geographic miss as well as increased toxicity when treating in a large single fraction, however these concerns have not been substantiated in published clinical outcomes. 5 In fact, several randomized single-vs multifraction trials for peripheral early stage NSCLC reported no significant difference in outcomes with long-term follow-up. 6 , 7 MR-guided SABR could facilitate broader use of single-fraction treatment by providing increased operator confidence in the accuracy of beam delivery to the target lesion throughout treatment by means of continuous intrafraction visualization with cine-MR. 13 Moreover, the streamlined workflow for treating in BH, or gated free breathing, without fiducial markers can substantially reduce the volume of normal tissue unnecessarily irradiated, and thus decrease the potential risk for serious toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…15 Image guidance, immobilization techniques, and motion management strategies have since evolved that facilitate the use of singlefraction SABR, which has the advantages of increased patient convenience, reduced cost, increased departmental patient throughput, and potential synergy with immunotherapy. 5 In the COVID-19 pandemic, we were prompted to treat selected patients with a single fraction to minimize exposure of patients to the hospital environment and thus the risk of SARS-CoV-2 infection, as well as to reduce our staffing and personal protective equipment needs when both of those resources were already constrained.…”
Section: Discussionmentioning
confidence: 99%
“…[31,32] Based on this background, we hypothesized to investigate a dose escalated SBRT schedule which is currently ongoing at our department, aiming also to reduce the sessions, in agreement with the growing literature in support of the single-fraction treatment of oligometastases. [33,34]…”
Section: Discussionmentioning
confidence: 99%
“…Future studies using MR-guided single-fraction SABR was recommended for the treatment of central lung cancers and liver metastases close to the portal vein and gastrointestinal tract. 11 …”
Section: Discussionmentioning
confidence: 99%